Eksistensi Pendidikan Agama: (Studi Tentang Realitas Sosial dan Status Guru Dalam Pendidikan Agama) - Raikhan, Raikhan (MADINAH, 2015)
There is an exaggerated but realistic worry that the author felt before writing this paper, after several times hearing and discussing with some fellow practitioners of education about a phrase that says "If pengin kaya, do not rely from ngguru alone ..." or even "if want to be rich, yo do not be a teacher! ". To understand a society, it can not be done at once as a whole because society is formed by various aspects. Those aspects are the realities that make up society. If society is likened to a house, then the parts that make up it are pole, wall, roof, foundation, and so on. Likewise society, composed of various social realities. To understand a society, we must understand the various social realities that constitute that society, including Master.